DBU Promoted Polysubstituted Arene Formation via a Michael Addition/Cyclization/Elimination Cascade Reaction - Guishun Bai; Yang Yang; Xingyue Wang; Jiamin Wu; Hong Wang; Xinyi Ye; Xiaoze Bao (Molecules, 2022)
The straightforward construction of polysubstituted arenes is essential in both synthetic chemistry and medicinal chemistry. Herein, we reported a DBU promoted Michael addition/cyclization/elimination cascade reaction between vinylogous malononitrile derivatives and chlorinated nitrostyrenes for the synthesis of polysubstituted arenes. The method features mild reaction conditions, wide substrate scope and high yield. Interestingly, preliminary study of the enantioselective version of this cascade was conducted to give chiral biaryl atropisomers with up to 40% ee through center-to-axial chirality transfer strategy.